Electricity in the 17th and 18th centuries: a study in early modern physics - Heilbron, J. L. (New York Dover publications, 1999)
After examining the principles and individuals underlying the early advancement of physics, Heilbron discusses the scientific development of electricity as its roots in the theories and discoveries of pioneer physicists